2022-RA-1076-ESGO Low pressure laparoscopic procedures in morbidly obese gynecological patients using a new subcutaneous abdominal wall-retraction device: a safety and feasibility study. (20th October 2022) - Ditto, Antonino; Roberti Maggiore, Umberto Leone; Granato, Vincenzo; Martinelli, Fabio; Chiappa, Valentina; Lopez, Salvatore; Signorelli, Mauro; Maruccio, Matteo; Palladino, Simona; Chiarello, Giulia; Bascio, Ludovica Spanò; Raspagliesi, Francesco
Abstract : Introduction/Background: Laparoscopic surgery for female patients with high BMI is still challenging despite it has been shown safe in obese patients. According to available literature, laparoscopic to laparotomic conversion rate in these patients is 57%, mostly for inadequate surgical exposure and anaesthetics indications. The aim of this prospective study is to assess feasibility, laparotomic conversion rate and perioperative complications after low-pressure laparoscopy (LPL) using a new subcutaneous abdominal wall-retraction device (LaparoTenser) in morbidly obese patients with gynecological diseases. Methodology: Inclusion criteria were: patients aged > 18 years, with BMI >30 kg/m2 who were eligible for laparoscopic surgery for gynaecological disease. We excluded patients with preoperative diagnosis of extra-uterine disease and contraindication to upfront general anesthesia/mini-invasive surgery. Anamnestic, surgical, postoperatively complications and hospitalization related data were prospectively collected. Results: We enrolled 24 patients since October 2020 to May 2022. table 1 summarizes the main characteristics of patients included in the study. The operating field visualization was optimal in 23 out 24 cases (95.8%) with a median (range) CO2 pressure of 3 (3–5) mmHg. Conversion rate for inadequate exposure was 4.1% (1/24). 2/24 patients underwent laparotomic conversion to be radically treated because of advanced disease. Operative time, blood loss, and hospital stay were similar to standard laparoscopy. No intraoperative complication or complication requiring second surgery was reported. One hematoma related to insertion of the subcutaneous needle of the wall lifter occurred and solved spontaneously. Early complications rate was 4.1% considering Dindo Classification ≥ 2. Conclusion: LPL with LaparoTenser device is a feasible and safe technique. The subcutaneous retractor may assist both surgeon and anaesthesiologist creating a large intra-abdominal operative space using low-pressure, reducing hemodynamic and respiratory risks due to high pressure and consequently the conversion risk. Further studies could confirm our results.